Social Justice Theories and Refugee Resettlement in New Zealand: A Content Analysis of Political Party Positions 2001-2017 - Mohamed, Mohamud Hassan (Auckland University of Technology, 2018)
With the increase in the number of refugees displaced over the past few years, so has there has been an increase in debate over whether liberal countries should do more to resettle refugees. This thesis conducts a qualitative content analysis of the policy debate in New Zealand over the last 16 years from 2001-2017 by looking at the stances that different political parties have taken in relation to the debate of resettling refugees. In particular, the debates are analysed in order to assess the extent to which theories of social justice might be reflected across the different policy positions of the parties studied in the research. In order to address the research question the perspectives and policies of four major political parties are examined: Labour, National, the Greens, and New Zealand First. Furthermore, to help answer the research question the study examines the policy positions of the parties through the lens of three significant events or ‘flash points’ which sparked political debate about New Zealand’s refugee resettlement policies between 2001 and 2017. The first event was the 2001 Tampa refugee crisis, followed by the case of Algerian political refugee Ahmed Zaoui who came to New Zealand in 2002. The continuing Syrian refugee crisis which came as a result of the Syrian civil war since 2011 is the final flash point examined in the thesis. In addition, to help answer the research question the views of four different theories are analysed carefully. Firstly the arguments made by liberal philosophers who state that a liberal human rights perspective needs to be taken when considering refugees for resettlement are examined in detail. Moreover, the perspectives of the libertarian, cosmopolitan and communitarian schools of thought are analysed. It is important to note, however, that this thesis gives particular weight to the arguments made from a liberal human rights viewpoint. The reason for this is that liberal human rights perspectives often iii guide the way that political parties in New Zealand and members of the international community react to each other and how they respond to global emergencies like the present refugee crisis. The study finds that most parties in New Zealand adopted policies that reflected arguments made from a liberal human rights perspective. Nevertheless, all parties at times changed their policies depending on the flash point for various reasons and consequently the policies they adopted mirrored different and sometimes contrasting social justice theories.
Keywords: Social Justice Theories; Refugee; Resettlement; New Zealand; Content Analysis; Political Party Positions